Credit Value-Relevance of Earnings, Other Comprehensive Income, and Comprehensive Income: A Study on IFRS Adoption Stage in Indonesia - Harjanti Widiastuti; Elsi Safira (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
This research aims to examine the credit value-relevance of net income, other comprehensive income (OCI) and comprehensive income. This research indirectly examines the impact of IFRS adoption on the usefulness of earnings and OCI information. The credit value-relevance measures the usefulness of accounting information from the creditor perspective, represented by the bond rating agency. In this research, accounting information is said to have credit value-relevance if accounting information affects bond rating. The sample of this research is 495 bond issuer companies listed in Indonesia Stock Exchange period 2011-2016. Hypothesis testing is done by the logit regression test. The results show that net income and comprehensive income have credit-value relevance, whereas OCI has no credit relevance. The results also find an increase in the credit-value relevance of comprehensive income from the beginning adoption of IFRS (2011) to the first implementation of IFRS adoption.